THE PREDICTION OF THE TWO-AXLES DEVELOPMENT OF FREIGHT CAR TRUCK - Myamlin, S. V.; Matsuk, A. S. (Science and Transport Progress, 2009)
The mathematical methods of calculation and analysis of patent fund enable estimation of progress of technical object trends. Using these methods, certain directions of development of biaxial bogie of freight carriage, in particular promising ones and directions, which exhausted the potential, are determined.